The Effectiveness of Online Reading Programme on Improving Reading and Writing Proficiencies: A Case Study of First-Year English Second Language Students at a University in the Gauteng Province, South Africa - Morongoa Theresia Mashitisho; Patricia Namayammu Mokgosi; Khashane Stephen Malatji (E-Journal of Humanities, Arts and Social Sciences)
Rapid technological advancement has facilitated the onset of online reading programmes as useful tools for enhancing the academic writing and reading comprehension skills of English Second Language (ESL) students. This study examined the effectiveness of an online reading programme, Programmed English Reading and Language System (PERLS), on the academic writing and reading comprehension of first-level English Second Language students. The study adopted the Social Constructivist Theory and used a qualitative case study design based on the interpretive paradigm. Five student development support (SDS) practitioners who served as the programme’s facilitators and 15 students who took part in the programme were purposively selected to participate in the study. Data was analysed using a qualitative content analysis. The results showed that PERLS can be used as a tool to assist ESL students enhance their reading and writing skills. The participants recommended that the PERLS’s duration be extended and accessible through several browsers so that students can use any browser that works for them. To ensure that the students gain better knowledge of PERLS facilitators should provide the students with an overview and explanation of the programme before its commencement. The results showed that PERLS is an effective teaching and learning programme, and it should be offered to as many students as possible. The study seeks to enhance understanding of the use and benefits of internet-based reading programmes in enhancing the reading and writing proficiencies of ESL students in institutions of higher learning.